Community crime prevention in Portugal: an introduction to Local Safety Contracts - Amante, Ana (Crime prevention and community safety, 2021)
Following the philosophy of other international programs as proximity policing or situational crime prevention, the Local Safety Contracts (CLS) have been an innovative strategy in Portugal, as they allow the sharing of accountabilities between the central and the local administration, in association with the police and the community. Nonetheless, little has been written in Portugal about such strategies, and nothing at all for the international scientific community. The aim of this paper is therefore to present the CLS, discussing their crime prevention stance and their impacts on local communities. First, the new preventive and multidisciplinary organizational model that is at the basis of CLS is discussed. Then a qualitative assessment of implementation is made through a set of interviews to relevant actors. Conclusions are drawn based on the experiences of municipalities, police and administration, contributing to the debate on community crime prevention, and enhancing the need for multidisciplinary, multilevel and place-specific approaches.